2018
DOI: 10.1017/s0033291718001253
|View full text |Cite|
|
Sign up to set email alerts
|

Perimenstrual exacerbation of symptoms in borderline personality disorder: evidence from multilevel models and the Carolina Premenstrual Assessment Scoring System

Abstract: Females with BPD may be at elevated risk for perimenstrual worsening of emotional symptoms. Longitudinal studies with fine-grained hormonal measurement as well as hormonal experiments are needed to determine the pathophysiology of perimenstrual exacerbation in BPD.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 65 publications
0
40
0
Order By: Relevance
“…Therefore, the backward counting method is particularly well suited for determining an individual’s time of ovulation, her early-to-mid luteal phase, and her premenstrual phase. In line with previous literature [55,56], for studies in the present review that provide onset of next menses and onset of prior menses, we characterized three of the cycle phases more precisely: ovulatory (cycle days −15 to −12), early-to-mid luteal (cycle days −11 to −8), and premenstrual (cycle days −7 to −1).…”
Section: Methodsmentioning
confidence: 69%
“…Therefore, the backward counting method is particularly well suited for determining an individual’s time of ovulation, her early-to-mid luteal phase, and her premenstrual phase. In line with previous literature [55,56], for studies in the present review that provide onset of next menses and onset of prior menses, we characterized three of the cycle phases more precisely: ovulatory (cycle days −15 to −12), early-to-mid luteal (cycle days −11 to −8), and premenstrual (cycle days −7 to −1).…”
Section: Methodsmentioning
confidence: 69%
“…It is likely that psychotropic medication and other biological markers may have influenced daily diary ratings (e.g. hormonal changes; Eisenlohr-Moul, DeWall, Girdler, andSegerstrom, 2015, 2018), which should be controlled for in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Complete details of recruitment and procedures for this sample are presented in Eisenlohr-Moul et al (2018). Listservs, flyers, and social media advertisements were used to recruit "females with emotional and interpersonal problems that interfere with life"; no materials involved references to the menstrual cycle to avoid self-selection bias.…”
Section: Methodsmentioning
confidence: 99%
“…Two studies demonstrated links between reproductive hormone changes and BPD feature expression in non-clinical samples (DeSoto, Geary, Hoard, Sheldon, & Cooper, 2003;Eisenlohr-Moul, DeWall, Girdler, & Segerstrom, 2015). Only one study to date has examined cycle effects on symptoms in a sample (N=15) of unmedicated cycling participants diagnosed with BPD (Eisenlohr-Moul et al, 2018). Despite the majority of the sample describing themselves in retrospective reports as experiencing low levels of premenstrual or menstrual symptom changes, in prospective daily assessments, many emotional and behavioral symptoms demonstrated a clear pattern of perimenstrual exacerbation across the sample, with high arousal symptoms such as irritability and anger rising in the luteal phase and peaking in the perimenstrual phase.…”
Section: Menstrual Cycle Effects In Borderline Personality Disordermentioning
confidence: 99%
See 1 more Smart Citation